2017
DOI: 10.1016/j.bpj.2017.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Mechanotransduction-Induced Reversible Phenotypic Switching in Prostate Cancer Cells

Abstract: Phenotypic plasticity is posed to be a vital trait of cancer cells such as circulating tumor cells, allowing them to undergo reversible or irreversible switching between phenotypic states important for tumorigenesis and metastasis. While irreversible phenotypic switching can be detected by studying the genome, reversible phenotypic switching is often difficult to examine due to its dynamic nature and the lack of knowledge about its contributing factors. In this study, we demonstrate that culturing cells in dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…In some cases, individual molecules are responsible when cellular tension in response to ECM rigidity exposes a cryptic signaling molecule or unfolds a propeptide chain; in some other cases, the strain in the cyto-structure can regulate receptor-ligand interaction to affect enzyme activity or, control a mechanosensitive ion channel [ 17 , [23] , [24] , [25] ]. Also, other physical parameters such as change in nuclear volume and shape [ 26 , 27 ], cell membrane curvature [ 28 , 29 ], fluid permeation [ 30 ], plasticity [ 31 , 32 ] etc. play significant roles in different scenarios where physical cues are converted into biochemical responses at a cellular level.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, individual molecules are responsible when cellular tension in response to ECM rigidity exposes a cryptic signaling molecule or unfolds a propeptide chain; in some other cases, the strain in the cyto-structure can regulate receptor-ligand interaction to affect enzyme activity or, control a mechanosensitive ion channel [ 17 , [23] , [24] , [25] ]. Also, other physical parameters such as change in nuclear volume and shape [ 26 , 27 ], cell membrane curvature [ 28 , 29 ], fluid permeation [ 30 ], plasticity [ 31 , 32 ] etc. play significant roles in different scenarios where physical cues are converted into biochemical responses at a cellular level.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated serum levels of GDF15 have been found in metastatic prostate cancer patients and is strongly associated with poor clinical outcome 37 . Furthermore, it has been recently demonstrated that GDF15 expression may be regulated by mechanotransduction and that GDF15 expression increases in palisading cancer cells from xenograft samples 37 , 38 . Together, these suggest that GDF15 expression could be affected by the environment during invasion and may serve as a marker of active invasion.…”
Section: Resultsmentioning
confidence: 99%
“…The assembly of these complexes allow for the activation of focal adhesion kinase (FAK) signalling, leading to cytoskeleton contractility and downstream activation of certain transcription factors and thus, gene expression. Studies in epithelial malignancies demonstrate that mechanotransduction can promote cancer cell proliferation, plasticity, chemoresistance, migratory, and metastatic properties and stemness [ 74 , 75 , 76 , 77 , 78 ].…”
Section: Mechanotransduction In Cancermentioning
confidence: 99%